Zawartość pierwiastków śladowych (Mn, Zn, Cu, Cd, Pb i Cr) w liściach olsz (alnus sp.) zastosowanych jako gatunki fitomelioracyjne na składowisku odpadów paleniskowych = Concentration of trace elements (Mn, Zn, Cu, Cd, Pb and Cr) in alder (alnus sp.) leaves used as phytomelioration species on fly ash disposal - Pietrzykowski, Marcin; Krzaklewski, Wojciech; Woś, Bartłomiej (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The paper presents concentration of selected trace elements (Mn, Zn, Cu, Cd, Pb and Cr) in the leaves of green, grey and black alders, introduced experimentally as phytomelioration species on fly ash disposal "Lubień" (in Central Poland, PGE "Bełchatów" Power Plant). The largest accumulation of the trace elements by alder species was noted in case of zinc, manganese and copper.
Keywords: popioły; odpady paleniskowe; olsza; pierwiastki śladowe; fly ash disposal site; alder; trace elements